Diabetic retinopathy risk in patients with unhealthy lifestyle: A Mendelian randomization study - Su, Zixuan; Wu, Zhixin; Liang, Xueqing; Xie, Meng; Xie, Jia; Li, Huiqing; Wang, Xinghua; Jiang, Fagang (Frontiers in Endocrinology, 2023)
Purpose This study aimed to investigate the causal association between unhealthy lifestyle factors and diabetic retinopathy (DR) risk and to determine better interventions targeting these modifiable unhealthy factors. Design Two-sample Mendelian randomization (MR) analysis was performed in this study. The inverse variance-weighted method was used as the primary method. Method Our study included 721 single-nucleotide polymorphisms associated with unhealthy lifestyle factors as instrumental variables. Aggregated data on individual-level genetic information were obtained from the corresponding studies and consortia. A total of 292,622,3 cases and 739,241,18 controls from four large consortia (MRC Integrative Epidemiology Unit [MRC-IEU], Genetic Investigation of Anthropometric Traits [GIANT], GWAS & Sequencing Consortium of Alcohol and Nicotine Use [GSCAN], and Neale Lab) were included. Result In the MR analysis, a higher body mass index (BMI) (odds ratio [OR], 95% confidence interval [CI] = 1.42, 1.30–1.54; P < 0.001] and cigarettes per day (OR, 95% CI = 1.16, 1.05–1.28; P = 0.003) were genetically predicted to be causally associated with an increased risk of DR, while patients with higher hip circumference (HC) had a lower risk of DR (OR, 95% CI = 0.85, 0.76–0.95; P = 0.004). In the analysis of subtypes of DR, the results of BMI and HC were similar to those of DR, whereas cigarettes per day were only related to proliferative DR (PDR) (OR, 95% CI = 1.18, 1.04–1.33; P = 0.009). In the MR-PRESSO analysis, a higher waist-to-hip ratio (WHR) was a risk factor for DR and PDR (OR, 95% CI = 1.24, 1.02–1.50, P = 0.041; OR, 95% CI = 1.32, 1.01–1.73, P = 0.049) after removing the outliers. Furthermore, no pleiotropy was observed in these exposures. Conclusion Our findings suggest that higher BMI, WHR, and smoking are likely to be causal factors in the development of DR, whereas genetically higher HC is associated with a lower risk of DR, providing insights into a better understanding of the etiology and prevention of DR.